Combination of LC-MS2 and GC-MS as a Tool to Differentiate Oxidative Metabolites of Zearalenone with Different Chemical Structures. (15th May 2012) - Hildebrand, Andreas A.; Pfeiffer, Erika; Damm, Georg; Metzler, Manfred
Abstract : Recent studies on the mammalian and fungal metabolism of the mycotoxin zearalenone (ZEN) have disclosed the formation of six regioisomers of monohydroxy-ZEN and its reductive metabolite zearalenol (ZEL). Hydroxylation occurs at the aromatic ring or at one of four positions of the aliphatic macrocycle. In addition, an aliphatic ZEN epoxide, its hydrolysis product, and other products were identified in fungal cultures. In this paper, we report the product ion spectra of the [M-H] − ions of 22 oxidative metabolites of ZEN and ZEL, obtained by LC-MS 2 analysis using a linear ion trap mass spectrometer with negative electrospray ionization. The MS 2 spectra exhibit qualitative and quantitative differences which allow a clear distinction of most metabolites. Moreover, GC-MS analysis of the trimethylsilylated metabolites yields electron impact mass spectra with numerous fragment ions which can be used as fingerprint to confirm the chemical structure derived by LC-MS 2 analysis.